Temporal variation of diabetic ketoacidosis and hypoglycemia in adults with type 1 diabetes: A nationwide cohort study: 在成年1型糖尿病中糖尿病酮症酸中毒与低血糖随时间变化情况:一项全国性的队列研究. (4th November 2015) - Butalia, Sonia; Johnson, Jeffrey A.; Ghali, William A.; Southern, Danielle A.; Rabi, Doreen M.
Abstract: Background: Seasonality in health outcomes has long been recognized for conditions such as colds and flus. The aim of the present study was to determine whether hospitalizations for acute complications of type 1 diabetes (T1D) vary by month and season. Methods: An observational study was performed of national administrative health data. Hospitalizations for acute complications in adults (aged ≥18 years) with T1D were identified using ICD‐10 (Canadian revision) codes between 2004 and 2010. Monthly and seasonal counts per year were determined for the study period. For each acute complication, the ratio of the number of observed hospitalizations/expected number of hospitalizations was calculated for each month and season per year, adjusting for varied lengths of month, season, and year. Results: In all, there were 21 568 hospitalizations for diabetic ketoacidosis (DKA) and 5349 hospitalizations for hypoglycemia during the study period. December had higher than expected hospitalizations for DKA and March had higher than expected hospitalizations for hypoglycemia. There did not appear to be variation for either DKA or hypoglycemia hospitalizations by season. Conclusions: The results of the present study suggest temporal variation in hospitalizations for DKA and hypoglycemia, and therefore signal important times of patient vulnerability. Potential mechanisms underlying this pattern warrant further examination. Prevention strategies and resources for patients with T1D may need to be increased at specific times during the year.